EVALUATION OF SUSTAINABLE DEVELOPMENT POLICY IN URBAN AREAS: A CASE STUDY IN MAKASSAR - Syafaruddin, Syafaruddin; Natsir, Nurasia; Syafaruddin, Andi Riska Andreani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to evaluate the effectiveness of sustainable development policies in Makassar and the public's perception of the impact of these policies on quality of life. The method used in this research is a quantitative approach, with data collected through a survey questionnaire distributed to 200 randomly selected respondents from various neighbourhoods in Makassar. The analysis results show that 80% of respondents have noticed improvements in air quality in their environment since the implementation of sustainable development policies, indicating a positive impact of these policies on environmental conditions. However, the results also reveal that 25% of respondents still experience dissatisfaction regarding accessibility to public facilities, highlighting challenges that need to be addressed to enhance the inclusiveness of these policies. Hypothesis testing indicates a significant positive effect between sustainable development policies and public perception of quality of life (H1). Moreover, the second hypothesis (H2), which states that community participation and government transparency influence policy effectiveness, is also accepted. These findings emphasize that community involvement and information openness are key factors in enhancing the success of sustainable development policies. This study recommends the necessity for ongoing evaluation and improved accessibility to public facilities to ensure that the benefits of the policies can be equitably felt by all segments of society. Thus, this research is expected to contribute to the development of more responsive and inclusive policies in the future.